IMPLEMENTASI CUSTOMER-BASED BRAND EQUITY MODEL DALAM MENINGKATKAN PEMANFAATAN PELAYANAN KESEHATAN DI PUSKESMAS SUNGAI RAMBUTAN, KABUPATEN OGAN ILIR, 2011 - Iwan Stia Budi; A. Fickry Faisya (Jurnal Ilmu Kesehatan Masyarakat, 2012)
Purpose of study was formulate recommendation to improving the utilization of Sungai Rambutan Public Health Center through Customer-Based Brand Equity Model. This study used descriptive study. Result : Brand awareness about sungai rambutan: Sungai Rambutan public health center as free health services, health services  no reliable, no guarantee of healing, infrastructure incomplete ,the discipline of work  less and not had willingness to visit sungai rambutan public health center if they were sick.